Ka mura ka muri: understandings of organ donation and transplantation in Aotearoa New Zealand. Issue 4 (22nd March 2021) - Shaw, Rhonda; Webb, Robert
Abstract : In this article, we refer to the separation of solid organs from the body as bio-objects. We suggest that the transfer of these bio-objects is connected to emotions and affects that carry a range of different social and cultural meanings specific to the context of Aotearoa New Zealand. The discussion draws on research findings from a series of qualitative indepth interview studies conducted from 2008 to 2013 with Māori (the Indigenous people of Aotearoa New Zealand) and Pākehā (European settler New Zealanders) concerning their views on organ donation and transplantation. Our findings show both differences and similarities between Māori and Pākehā understandings of transplantation. Nevertheless, while many Māori draw on traditional principles, values and beliefs to reflect on their experiences in relation to embodiment, gift-giving, identity and well-being, Pākehā tend to subscribe to more Western understandings of identity in terms of health and well-being, in line with international literature on the topic. Rather than reflecting individualistic notions of the body and transplantation as the endpoint of healthcare as do Pākehā, Māori views are linked to wider conceptions of family, ancestry and belonging, demonstrating how different rationalities and ontologies affect practices and understandings surrounding organ transfer technology. In the article, we focus predominantly on Māori perspectives of organ transfer, contextualising the accounts and experiences of our research participants against the backdrop of a long history of settler colonialism and health inequalities in Aotearoa New Zealand.